2014
DOI: 10.1021/la5037053
|View full text |Cite
|
Sign up to set email alerts
|

Brownian Motion of Arbitrarily Shaped Particles in Two Dimensions

Abstract: We implement microfabricated boomerang particles with unequal arm lengths as a model for nonsymmetric particles and study their Brownian motion in a quasi-two-dimensional geometry by using high-precision single-particle motion tracking. We show that because of the coupling between translation and rotation, the mean squared displacements of a single asymmetric boomerang particle exhibit a nonlinear crossover from short-time faster to long-time slower diffusion, and the mean displacements for fixed initial orien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 61 publications
3
93
1
Order By: Relevance
“…For example, when the tensor rank is one (i.e. when B is a vector), we find three eigenvalues −f (1) i (as in Ref. [11]), with…”
Section: Evolution Due To Rotational Diffusionsupporting
confidence: 51%
See 1 more Smart Citation
“…For example, when the tensor rank is one (i.e. when B is a vector), we find three eigenvalues −f (1) i (as in Ref. [11]), with…”
Section: Evolution Due To Rotational Diffusionsupporting
confidence: 51%
“…Brownian motion of particles with arbitrary shapes has been recently investigated in many different contexts, including proteins, DNA, nanofibers, actins or other biological nano and micro objects [1][2][3][4][5][6][7]. There is a rapidly growing number of experimental and numerical studies, which give rise to interesting fundamental questions, challenging for theoreticians.…”
Section: Introductionmentioning
confidence: 99%
“…Some asymmetry may also be incorporated into the crowder shape. Recently, single-particle tracking measurements allowed one to rationalise the translational and rotational diffusivities of micron-size symmetric and asymmetric boomerang-shaped particles in two dimensions [133]. It was observed that the regimes of Brownian diffusion exist at short and long times while a coupling of D and D r gave rise to subdiffusion at intermediate times.…”
Section: Discussionmentioning
confidence: 99%
“…This is different for particles without any symmetry axis. 30,52 In such situations, an intricate interplay between the gravitational effects resulting from an inhomogeneous mass distribution as reported in the present article and gravitactic behavior due to the shape asymmetry 32 will govern the particle dynamics.…”
Section: Discussionmentioning
confidence: 65%